PEMANFAATAN WAYANG LINGUA DALAM MEMBERANTAS BUTA BAHASA INDONESIA DAN BUTA AKSARA DI DESA TERPENCIL BODAG - Nur’aini, Neni; Armianto, Muhammad Slamet; Triyanto, Agus (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Bodag village is a secluded village in Madiun Regency, most of the people are still illiterate, they also can not speak Indonesian language, it occurs due to their lack of facilities in educational purpose and their awareness of the importance of education is still low. But the villagers of Bodag have potential in arts, especially the puppets and folk musical. Therefore, the idea of making âWayang Linguaâ came up as media that is used to fight against illiteracy in Bodag village. âWayang Linguaâ come from the word Wayang and Lingua, lingua means language. Here, the performance of Wayang Lingua used as a method, while people watching the performance, the indirectly learning how to use Indonesian language and how to speak the language itself, they can also learn how to write the letter of alphabet. Thatâs the value that is indirectly inserted from the performance of Wayang Lingua.